Anthropometric characteristics of Indian volleyball players in relation to their performance level - Amandeep Sıngh; Vishaw Gaurav (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to find out the differences in anthropometric characteristics of volleyball players in relation to their performance level (i.e., inter-university and inter-college). For this study, two hundred and forty (N=240) male volleyball players (inter-university level, N1=120, inter-college level, N2=120) of age ranging from 18-25 years were selected as subjects from various colleges and universities of North India. The purposive sampling technique was used to select the subjects. All subjects were assessed for height, weight, lengths, circumference and diameters. The independent samples t-test revealed that inter-university volleyball players had significantly higher height (p lt;0.05), weight (p lt;0.05), leg length (p lt;0.05), lower leg length (p lt;0.05) than inter-college volleyball players. However, inter-college volleyball players had significantly greater forearm length (p lt;0.05). The inter-university volleyball players also had significantly greater upper arm circumference (p lt;0.05), forearm circumference (p lt;0.05), thigh circumference (p lt;0.05) and calf circumference (p lt;0.05) than inter-college volleyball players. The inter-university volleyball players had significantly wider elbow diameter (p lt;0.05), shoulder diameter (p lt;0.05) and lesser hip diameter (p lt;0.05) than inter-college volleyball players. It is concluded that there were significant differences between inter-university and inter-college volleyball players with regard to anthropometric characteristics. Inter-university players showed better anthropometric measurements as compared to inter-college volleyball player.